Intracervical PGE2 gel for induction of labour in patients with prelabour rupture of membranes with unfavorable cervix after 34 weeks period of gestation - Jayaprakash, Sheela; Muralidhar, Lakshmidevi; Venkatesh, Shreedhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Premature rupture of membranes (PROM) occurs in 5-10% of all pregnancies. Approximately 60% of cases of PROM occur in term patients. Intra-vaginal or intra-cervical PGE2 has been found to be efficacious in inducing labour at term with the majority of patients delivered with or without the aid of oxytocin, most within 24 hours. But the use of PGE2 gel in patients with PROM and unfavorable cervix to induce labour is not widely accepted possibly for fear of introduction of infection and for draining away the gel with liquor. The objective of this study was to evaluate the efficacy of prostaglandin E2 gel (Dinoprostone 0.5mg) for induction of labour in patients with PROM at term and 34-37 weeks of gestation with an unfavorable cervix. Methods: Study was performed at Vydehi Institute of Medical Sciences and Research Centre from February 2013 to June 2015. Eligible patients included those at term and 34 to 37 weeks of gestation with spontaneous rupture of membranes who presented before onset of labour. All patients had singleton pregnancy with vertex presentation. All patients received a single intra-cervical application of 0.5 mg PGE2 gel. If labour was not established at 6 hours, repeat cervical assessment was done and those with unfavorable cervix received 2nd dose of intra-cervical application of PGE2 gel. After an additional 6 hours, patients with low Bishop’s scores were tried with oxytocin titration infusion. Results: Of the 80 patients 68 patients (85%) began labour after single application, 12 patients (15%) required 2nd dose of PGE2. 22 patients (25%) required augmentation with oxytocin. 6 patients landed up with cesarean section. Mean interval between prostaglandin application and delivery was 11.5 hours. No significant maternal and neonatal infectious morbidity was seen in the study. Conclusions: Intra-cervical PGE2 gel is safe and effective for inducing labour in patients with PROM with unfavorable cervix. In our study we had high rate of vaginal delivery with no infectious morbidity.